2004
DOI: 10.1177/152692480401400410
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccine Antibody Responses in Lung Transplant Recipients

Abstract: Lung transplant recipients had lower influenza vaccine response rates than healthy individuals. Influenza vaccine antibody response is influenced by concomitant administration of mycophenolate mofetil or sirolimus. Future studies should measure protection from influenza infection conferred by immunization and alternative vaccination strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 23 publications
1
34
1
2
Order By: Relevance
“…The poor response to the vaccine documented in previous studies [22][23][24] and in the present study suggests that alternative prophylactic strategies may be needed. Potential alternative strategies not addressed in this study include vaccination of all close contacts of the transplant recipient and the use of anti-viral prophylaxis.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The poor response to the vaccine documented in previous studies [22][23][24] and in the present study suggests that alternative prophylactic strategies may be needed. Potential alternative strategies not addressed in this study include vaccination of all close contacts of the transplant recipient and the use of anti-viral prophylaxis.…”
Section: Discussionmentioning
confidence: 55%
“…Likewise, because hemagglutinin inhibition titers were not drawn as part of this study, the vaccine may have been matched to the strain, but not protective. Influenza vaccination has been associated with poor immunogenicity (4-fold antibody only seen in 19% to 43% 22,23 of patients and poor cell-mediated immune response, as judged by interleukin [IL]-2, IL-10, interferon-␥ and granzyme B). 24 The fact that patients had a relatively mild condition could also suggest that the vaccine contributed to partial protection and a milder course.…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous vaccine studies in LTRs have focused on documentation of serologic or cellmediated immune responses to influenza vaccines. [5][6][7][8] These studies have shown diminished serologic responses when compared with healthy subjects, thus raising the question of the predominant mechanism involved in vaccine-triggered protection. Due to the small number of infections in vaccinated LTRs we were unable to draw conclusions on vaccine effectiveness for one vs two vaccinations.…”
Section: Discussionmentioning
confidence: 96%
“…4 Studies have shown that LTRs have lower antibody responses compared with healthy individuals, and less consistent results have been noted when assessing cell-mediated immune responses to influenza vaccines. [5][6][7][8] Clinical or protective effectiveness, such as the ability of the vaccine to prevent infection, is the gold standard when assessing a vaccine in a specific population. Studies of the clinical effectiveness of influenza vaccination are lacking for recipients of SOT.…”
mentioning
confidence: 99%
“…68 Patienten mit bilateraler Lungentransplantation wurden unter Therapie mit MMF geimpft. Der Impferfolg war mit 43% der Patienten signifikant geringer als bei den 35 gesunden Kontrollen mit 63% [18]. Eine eingeschränkte Impfantwort zeigte sich auch bei 49 Patienten unter Immunsuppression mit Azathioprin oder MMF bei früherer Nierentransplantation.…”
Section: > Eine Influenzimpfung Ist Bei Allen Patientengruppen Gerechunclassified